2018
DOI: 10.1002/iub.1919
|View full text |Cite
|
Sign up to set email alerts
|

Can Mitochondrial DNA be CRISPRized: Pro and Contra

Abstract: Mitochondria represent a chimera of macromolecules encoded either in the organellar genome, mtDNA, or in the nuclear one. If the pathway of protein targeting to different sub-compartments of mitochondria was relatively well studied, import of small noncoding RNAs into mammalian mitochondria still awaits mechanistic explanations and its functional issues are often not understood thus raising polemics. At the same time, RNA mitochondrial import pathway has an obvious attractiveness as it appears as a unique natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 48 publications
6
41
0
1
Order By: Relevance
“…Our results show an enhanced delivery of gRNA with RP-loop. A recent study has shown that guide RNA with short hairpin structures can promote mitochondrial import and specific cleavage of mtDNA albeit at low level due to limited import into mitochondrial matrix (41,42). This study further strengthens our hypothesis that specific hairpin structures that are involved in the delivery of nuclear encoded RNA can serve as potential adapter for delivery and PNPase may serve as conduit for channeling this recombinant RNA into mitochondrial matrix.…”
Section: Discussionsupporting
confidence: 86%
“…Our results show an enhanced delivery of gRNA with RP-loop. A recent study has shown that guide RNA with short hairpin structures can promote mitochondrial import and specific cleavage of mtDNA albeit at low level due to limited import into mitochondrial matrix (41,42). This study further strengthens our hypothesis that specific hairpin structures that are involved in the delivery of nuclear encoded RNA can serve as potential adapter for delivery and PNPase may serve as conduit for channeling this recombinant RNA into mitochondrial matrix.…”
Section: Discussionsupporting
confidence: 86%
“…Because there is no natural mechanism for the import of RNA into mitochondria, the mechanism involved was puzzling. Extensive discussions on the possibility of having a CRISPR‐like system working in mammalian mitochondria have been discussed [49,50]. Again, the main limitation is the ability to import RNA into mitochondria, which in itself is a controversial topic [50].…”
Section: Mitochondria‐targeted Zinc‐finger Nucleasesmentioning
confidence: 99%
“…Extensive discussions on the possibility of having a CRISPR‐like system working in mammalian mitochondria have been discussed [49,50]. Again, the main limitation is the ability to import RNA into mitochondria, which in itself is a controversial topic [50]. The use of a CRISPR‐like architecture in mitochondria would be very powerful, particularly because of the recent advances in DNA base editing tools [51].…”
Section: Mitochondria‐targeted Zinc‐finger Nucleasesmentioning
confidence: 99%
“…The limitation on ubiquitous use of these systems is their two-component nature: RGENs include both protein and RNA parts. Successful delivery of RNA moieties into mitochondria (as a part of RGEN) is very complicated, but there is an experimental proof of its possibility (Jo et al 2015;Loutre et al 2018;Bian et al 2019) . Thus, in the future, there are all the prerequisites that mtDNA editing technology can be implemented, and even after some time, introduced into the clinic as ART, as it has happened with mitochondrial donation technology (Figure 2).…”
mentioning
confidence: 99%